2018
DOI: 10.1108/bpmj-11-2016-0232
|View full text |Cite
|
Sign up to set email alerts
|

Supporting business processes through human and IT factors: a maturity model

Abstract: Purpose The purpose of this paper is to assist organizations in the assessment of both information technology (IT) and human factors required to support their business processes (BPs) by taking into account the interdependence and alignment of these factors, rather than considering them independently. Design/methodology/approach A design science research methodology was followed to build a maturity model (MM) enabling this assessment. The proposed design process is composed of four steps: problem identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 37 publications
1
29
0
1
Order By: Relevance
“…Our model also highlights each of the different components within the human and technology categories that SMEs need to pay due attention if they wish to enhance the effectiveness of the people practices in contributing value of their internationalisation (xxx, 2019). In fact, this study extends all these conceptualisations as the model developed here has been shown to be competent to compare different types of barriers, aspects that have not been previously studied (see Mamoghli et al, 2018). In general, both people and technological oriented barriers seem to be likewise significant at 83% overall variance for SMEs in a developing country context such as Bangladesh.…”
Section: Summary Of Findingssupporting
confidence: 59%
See 1 more Smart Citation
“…Our model also highlights each of the different components within the human and technology categories that SMEs need to pay due attention if they wish to enhance the effectiveness of the people practices in contributing value of their internationalisation (xxx, 2019). In fact, this study extends all these conceptualisations as the model developed here has been shown to be competent to compare different types of barriers, aspects that have not been previously studied (see Mamoghli et al, 2018). In general, both people and technological oriented barriers seem to be likewise significant at 83% overall variance for SMEs in a developing country context such as Bangladesh.…”
Section: Summary Of Findingssupporting
confidence: 59%
“…Secondly, once the right types of employees that need to be included are available, they should be motivated using the 'best practices' that are perceived to yield an increase in performance (Paul and Anantharaman, 2003). If this does not work, Patterson et al, (1997) and others advised a (re-) organisation of not only the people activities but also work and information sharing processes involved so as to benefit from outputs (Perkins and White, 2011;Armstrong, 2015), something sorely missed by Dar and Mishra (2019), Booltink and Saka-Helmhout (2018) and Mamoghli et al, (2018). This might include a firm's financial profitability and people's preferences (Campbell andvan Wanrooy, 2013 Perkins andWhite, 2011) as well as the extent to which people and non-people aspects interact (Marsden and Dickinson, 2013;Gerhart and Fang, 2005).…”
Section: Conceptual Model Developmentmentioning
confidence: 99%
“…Os funcionários podem usar o modelo proposto ao longo de sua jornada em direção à excelência do processo. A aplicação desse modelo leva a dois cenários principais de melhoria de processos: aprimoramento da sofisticação e integração das tecnologias de software em suporte aos processos e melhoria da coesão dos recursos que a organização já possuirecursos humanos e de TI (MAMOGHLI et al, 2018). Os processos que identificaram possibilidades de melhorias a serem implantadas foram listados e as ações de melhorias foram elencadas conforme o Quadro 1 abaixo.…”
Section: Discussões E Resultadosunclassified
“…A discussion within this category refers to identification and understanding of BI and BPM implementation and adoption CSFs in SMEs. Following the recommendations of Nguyen, Meredith and Burstein as well as Rockart, the CSFs are categorized into three groups 43,44 : (1) common, (2) 35 Ø Ø P P Ø Reher 36 Ø P Ø Ø P Rolinek et al 37 Ø P P P Ø Singer 38 Ø Ø P P P Braunnagel et al 8 Ø P P P Broccardo et al 39 P Ø Ø P Ø Bandara and Opsahl 4 P Ø Ø Ø P Lö ckmann and Feldmann 40 Ø P Ø Ø P Giacosa et al 41 P Ø Ø Ø P Mamoghli et al 42 P Ø P Ø P Business intelligence Dubravac and Bevanda 25 P Ø Ø P Ø Boonsiritomachai et al 6 P Ø P P Ø Raj et al 26 Ø P Ø Ø P Gauzelin and Bentz 27 Ø P Ø Ø P Adeyelure et al 28 Ø P Ø P Ø Gudfinnsson and Strand 29 P Ø P Ø P Llave et al 30 P Ø Ø Ø P Puklavec et al 31 P Ø Ø P Ø Popovič et al 32 P Ø Ø P Ø Raj et al 33 Ø P Ø Ø P…”
Section: Literature Review Discussionmentioning
confidence: 99%